2004
DOI: 10.1002/jsfa.2035
|View full text |Cite
|
Sign up to set email alerts
|

In vitro availability of starch in heat‐treated potatoes as related to genotype, weight and storage time

Abstract: The objective of the study was to determine the influence of potato variety, weight and storage time after lifting on the glycaemic index (GI) and resistant starch (RS) content predicted from measurement of the rate and extent of in vitro starch hydrolysis, respectively. The potatoes were either boiled, or boiled and subjected to different heat-cycling conditions selected to promote retrogradation of amylose or amylopectin, respectively. The hydrolysis indices (HI) and predicted GIs of all 19 potato products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
(28 reference statements)
3
24
0
1
Order By: Relevance
“…Data on french fries are based on manufacturer's data, whereas the remaining values are from food tables (Livsmedelsverket, 2001). The starch content in the potatoes was calculated by use of a formula stated by Leeman et al (2005), where a strong correlation between dry matter content and available starch content was found in boiled potatoes. In Table 1, there are also data on serving weight, meal volume, energy density and dry matter content.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Data on french fries are based on manufacturer's data, whereas the remaining values are from food tables (Livsmedelsverket, 2001). The starch content in the potatoes was calculated by use of a formula stated by Leeman et al (2005), where a strong correlation between dry matter content and available starch content was found in boiled potatoes. In Table 1, there are also data on serving weight, meal volume, energy density and dry matter content.…”
Section: Studymentioning
confidence: 99%
“…Remaining values from food tables (Livsmedelsverket, 2001). The starch content in the boiled potatoes was calculated by use of a formula stated by Leeman et al (2005). (Livsmedelsverket, 2001).…”
Section: Energy-equivalent Meals (Study 1)mentioning
confidence: 99%
“…Leeman et al (2005), using analytical methods developed by Å kerberg et al (1998) also found a significant increase of resistant starch in potatoes after extended time periods of temperature cycling at conditions known to favor amylose retrogradation.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro tests have also shown lower digestibility for cooled potato products (Garcia-Alonso and Gon˜i, 2000;Kingman and Englyst, 1994) and for temperature-cycled potatoes (Leeman et al, 2005). These all suggest to formation of type-3 resistant starch, when potatoes are stored at refrigerator temperatures after boiling or baking.…”
Section: Discussionmentioning
confidence: 96%
“…to linear for pure starch. There should be noted that retrogradation (reassociation of amylose/amylopectin chains that occurs during storage of gelatinized starch by means of hydrogen bonds) can lower the digestibility of starch due that its structure turns less accessible to digestive enzymes, so glycemic response of retrograded starch is more moderated than of gelatinized starch (Rosin, Lajolo, & Menezes, 2002;Karlsson & Eliasson, 2003;Fernandes et al, 2005;Leeman, Bårström, & Björck, 2005;Morita et al, 2005;Burton and Lightowler, 2008). Due to this, the linearity between DG and glycemic response is probably lost or the curve slope could be modified if retrograded starch is present (Chung, Lim, & Lim, 2006).…”
Section: In Vivo Glycemic Responsementioning
confidence: 94%